PENGARUH EFEKTIFITAS DAN EFISIENSI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN BANGGAE TIMUR - SHOFIANA SYAM (Universitas Muhammadiyah Makassar, 2020)
To get a maximum result or an effective and efficient team work certainly requires good communication between individuals in an organization. Effectiveness Is a measure of an organization in achieving better work processes in completing tasks. Work efficiency is the best comparison between the work done and the results achieved by the work in accordance with those targeted both in terms of quality and results. The research conducted at the East Banggae Sub-district office uses multiple linear regression analysis methods. The study was conducted for 3 months, from January to March 2020. The results showed that: 1) there was a significant effect of effectiveness on the Performance of Employees at the East Banggae District Office, partially, 2) there was a significant effect of Work Efficiency on the Performance of Employees at the East Banggae District Office, partially, 3) there was a significant influence between effectiveness and efficiency of work on employee performance at the East Banggae sub-district office simultaneously and the results show that the value of the two variables affect the achievement of optimal employee performance.